Therapeutic effect of Periploca forrestii on collagen-induced arthritis in rats through JAK2/Nf-κB pathway - Zhenyi Zhang; Yingchun Li; Jian Wu; Jihong Zhang; Ning Chen; Ning Zhang (Frontiers Media S.A., 2024)
BackgroundRheumatoid arthritis (RA) is a chronic autoimmune disease that affects the body. Periploca forrestii was a miao ethnic drug in China that was used to treat arthritis for hundreds of years. But, the therapeutic mechanism is so far unknown. Therefore, the chemical component and effect of Periploca forrestii on arthritis in rats were studied using HPLC-QTOF MS, micro-CT, and other experiments in this paper.MethodMale Sprague-Dawley rats were used to assess the in vivo activity. HPLC QTOF-MS was used to analyze the chemical profile of the P. forrestii (PF). Bovine type II collagen and Complete Freund's Adjuvant were used to stimulate and construct the collagen-induced arthritis (CIA) model. Three dosages of PF (100 mg/kg, 200 mg/kg, 400 mg/kg) were used to evaluate in vivo activity. Methotrexate was used as the positive drug. H/E staining and micro-CT methods were used to monitor the pathological changes of CIA rats. ELISA method was used to assess the serum level of immune- and inflammation-related cytokines. Immunohistochemical experiments were used to test the gene expression in JAK and Nf-κB pathways.Results42 compounds were identified from PF. PF administration lowered the increased spleen index compared with that of control and MTX groups, and partially restored body weight, reduced paw swelling, and arthritis score compared with the model group. Macroscopic assessment indicated inflamed paw with significant swelling in the model group, while the extent of inflammation and swelling was attenuated by both MTX and PF. H/E staining experiments demonstrated that pathological changes of synovial cells and infiltration of inflammatory cells were observed in the model group. In contrast, the MTX and PF treatment partially reversed these pathological changes. Micro-CT examination showed severe injuries and scars caused by inflammation for the model group, and in the high-dosage group (400 mg/kg) the inflammation-caused injuries and scars were dramatically ameliorated. Mechanism study showed that PF restored Nf-κB phosphorylation and JAK2 expression compared with the model group.ConclusionP. forrestii possesses a potent effect on CIA rats. Nf-κB and JAK2 pathways are involved in its protective effect on CIA.